SISTEM PENYELESAIAN SENGKETA DENGAN HUKUM ADAT DI MASYARAKAT SUNDA WIWITAN - Mugig Setiawan Lindawati; Novia Kusuma Ningrum; Novka Augusti Sarrahisdas; Rafi Raihan Fadhillah (Pojok Publisher, 2025)
The dispute resolution mechanism of the Sunda Wiwitan indigenous community, which still upholds ancestral values amid modernization and the dominance of national law, tends to resolve conflicts through traditional institutions in a familial manner, prioritizing deliberation, mediation, and life philosophies such as silih asih (mutual love), silih asah (mutual sharpening), and silih asuh (mutual nurturing). This research employs a literature study to explore data on the effectiveness and challenges of customary law in addressing contemporary conflicts, particularly inheritance disputes. The findings indicate that the traditional dispute resolution system is restorative and more contextual, though it has weaknesses in terms of formal legality and written documentation. The study highlights the importance of strengthening cultural identity and educating the younger generation to preserve the existence of Sunda Wiwitan customary law within Indonesia's modern legal system.